KOMPARASI REGULASI PERLINDUNGAN DATA PRIBADI DI UNI EROPA DAN AMERIKA SERIKAT - Royan Hanapi; Owen Hutagalung; Widi Susanto; Indah Dewi Megasari (PT. Hasba Edukasi Mandiri, 2025)
This article presents a comprehensive comparison between the personal data protection regulatory frameworks of the European Union and the United States. The European Union adopts a comprehensive, rights-based approach through the General Data Protection Regulation (GDPR), emphasizing transparency, accountability, and individual control over personal data. In contrast, the United States employs a hybrid model that combines sector-specific federal regulations with state-level privacy laws such as the California Consumer Privacy Act (CCPA) and California Privacy Rights Act (CPRA), resulting in varying levels of protection across sectors and jurisdictions. This article examines key dimensions of both systems, including scope and extraterritorial reach, legal bases for data processing, data subject rights, obligations of data controllers, enforcement mechanisms, and the nature of sanctions. It also explores each system’s approach to cross-border data transfers and analyzes practical implications for global businesses, regulatory bodies, and individuals as data subjects. The findings indicate that the GDPR provides more stringent and harmonized safeguards, whereas the U.S. system offers greater flexibility but remains fragmented. The article concludes by highlighting the strengths and weaknesses of both regulatory models and offering policy recommendations aimed at strengthening data protection while supporting technological advancement and economic innovation in the digital era.